CONTESTED MEMORIES: NATIONALIST HISTORIOGRAPHY AND QUIT INDIA MOVEMENT - Lathwal, Sumit; Rani, Monika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This article explores the works of nationalist historians who have written about the Quit India movement. It focuses on the movement’s origin, aims, and significance from their perspectives. The Quit India movement holds great significance in the Indian National movement as it aimed for the immediate end of British rule in India as highlighted by Gandhi’s clarion call. This article analyzes how nationalist historians have interpreted the movement’s inception and Objectives, emphasizing the motivations behind its origin and the strategic aims it desired to achieve. By analyzing nationalist accounts of the event, it explores how these nationalist narratives have highlighted the movement’s emphasis on mass civil disobedience and its role in galvanizing widespread participation across different strata of the Indian state. Additionally, this article examines how nationalist historians have portrayed the impact of the movement on the course of the Indian freedom struggle.